2015
DOI: 10.1542/peds.2014-4025
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Therapy for Septic Arthritis in Children

Abstract: BACKGROUND AND OBJECTIVE: Prospective studies of children with septic arthritis report that adding dexamethasone to antibiotic therapy contributes significantly to clinical and laboratory improvement. This study sought to evaluate the effect of this regimen outside of a randomized controlled trial. METHODS:The sample consisted of children with septic arthritis hospitalized at a tertiary pediatric medical center in 2008 to 2013. Disease course and outcome were compared between children treated with antibiotics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
1
16
0
2
Order By: Relevance
“…Recent studies suggested a potential beneficial role for intravenous steroid administration in children with septic arthritis. 56,57 The introduction of new generation cephalosporins and the use of monoclonal antibodies directed against virulence factors of the causative pathogen could affect outcomes in future. 3 …”
Section: Treatment Of Acute Paediatric Osteoarticular Infectionsmentioning
confidence: 99%
“…Recent studies suggested a potential beneficial role for intravenous steroid administration in children with septic arthritis. 56,57 The introduction of new generation cephalosporins and the use of monoclonal antibodies directed against virulence factors of the causative pathogen could affect outcomes in future. 3 …”
Section: Treatment Of Acute Paediatric Osteoarticular Infectionsmentioning
confidence: 99%
“…Die SAG ist potenziell pyogen, wobei Streptococcus intermedius der pathogenste Keim der Gruppe ist. Er kann vor allem Abszess-Formationen in Hirn und Leber verursachen [2,4] und selten auch zu Endokarditis und Milzabszessen führen [4,5]. Typische Streptokokken-Virulenzfaktoren wie Hyaluronidase und Neuraminidase, die die Ausbreitung der Infektion begünstigen [2], wurden in Genomstudien identifiziert, funktionelle Studien der molekularen Basis fehlen jedoch [3].…”
Section: Septische Gonarthritis Und Ausgedehnter Wadenabszess Durch Sunclassified
“…1). [4]. Studien bei septischer Arthritis durch Streptococcus intermedius und DexamethasonTherapie liegen nicht vor.…”
Section: Fallberichtunclassified
“…DEX has been used to treat a broad range of inflammatory diseases, including Crohn's disease (Cully ), rheumatoid arthritis (Fogel et al. ), noninfectious uveitis (Tomkins‐Netzer et al. ), and asthma (Gries et al.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they activate transcription factors that induce expression of anti-inflammatory genes (Vandevyver et al 2013). DEX has been used to treat a broad range of inflammatory diseases, including Crohn's disease (Cully 2015), rheumatoid arthritis (Fogel et al 2015), noninfectious uveitis (Tomkins-Netzer et al 2014), and asthma (Gries et al 2000), among other conditions. Alternatively, glucocorticoids cause repression of genes encoding proinflammatory mediators, including cytokines, chemokines, and inflammatory adhesion molecules (van der Velden 1998).…”
Section: Introductionmentioning
confidence: 99%